197 Survival outcomes and toxicity among patients treated with concomitant radiotherapy and immunotherapy for advanced melanoma: two faces of the abscopal effect?. (9th November 2020) - Andreatos, Nikolaos; Roopkumar, Joanna; Khorana, Alok; Woody, Neil; Gastman, Brian; Funchain, Pauline
Abstract : Background: Combined treatment with radiotherapy (RT) and checkpoint inhibition (CPI) can theoretically increase both treatment response and toxicity. We recently reported a high rate of immune-mediated adverse events (irAEs) among patients with advanced melanoma and Merkel cell carcinoma (MCC) treated with concomitant RT and CPI. We now present survival data from the same cohort. Methods: The original study population consisted of 30 patients with advanced melanoma and 5 with MCC who underwent RT within 30 days of CPI; eligible patients were identified via an institutional retrospective registry. Information on the development of new irAEs diagnosed within 3 months of RT initiation was collected. Overall survival (OS) was calculated by the Kaplan-Meier method. Outcomes of patients who did or did not develop new irAEs after RT were compared via the log-rank test. To limit heterogeneity, the survival analysis was restricted to patients with melanoma. Results: Of the 30 patients with melanoma included in the survival analysis, 25 had died and 5 remained alive when data were censored in August 2020. Median follow-up was 18 months. Treatment with concomitant RT and CPI constituted first-line therapy for most patients (21/30); 8 patients had received one previous line of treatment and 1 patient had progressed on multiple regimens. Thirteen patients (43.3%) experienced at least one new irAE following RT in the context of concomitant CPI. Patients who experienced new irAEs post-RT demonstrated longer median OS of 25 months (95% confidence interval (CI): 8.6 - 41.4 months) in comparison to a median OS of 11 months for patients who did not develop post-RT irAEs (95% CI: 0.0 – 24.4 months). In the post-RT irAE group, 1-year and 2-year OS (69.2% and 53.8%, respectively) were higher compared to patients without irAEs (47.1% and 23.5%, respectively). These differences in survival did not reach statistical significance within this limited cohort size (figure 1 ; p = 0.076). Conclusions: The use of concomitant RT and CPI was associated with an elevated rate of new irAEs. Patients who developed new irAEs following RT experienced a substantial absolute increase in median OS of 14 months, an observation from a limited cohort which warrants further investigation. These data support prior reports of increased OS among patients experiencing irAEs and may suggest that RT and CPI in combination can meaningfully potentiate immune response in certain clinical contexts. Ethics Approval: The study was approved by the Cleveland Clinic Foundation Institutional Review Board, approval number 18–1225